Aspirin Resistance in Hypertensive Patients - ÖZBEN SADIÇ, BESTE (WILEY, 2010)
Aspirin resistance is associated with poor clinical prognosis. The authors investigated aspirin resistance in 200 hypertensive patients (111 men, age: 68.3 +/- 11.4 years) by the Ultegra Rapid Platelet Function Assay-ASA (Accumetrics Inc., San Diego, CA). Aspirin resistance was defined as an aspirin reaction unit >= 550. Aspirin resistance was detected in 42 patients. Aspirin resistance was present in 25.6% of the patients with poor blood pressure control, while in 17.8% of the patients with controlled blood pressure (P=.182). Female gender and creatinine levels were significantly higher (P=.028 and P=.030, respectively), while platelet count was significantly lower (P=.007) in aspirin-resistant patients. Multivariate analysis revealed that female gender (odds ratio [OR], 2.445; P=.045), creatinine levels (OR, 1.297; P=.015) and platelet count (OR, 0.993; P=.005) were independent predictors of aspirin resistance. The frequency of aspirin resistance is not low in hypertensive patients. Female hypertensive patients, especially, with higher creatinine levels and lower platelet count are at higher risk for aspirin resistance. J Clin Hypertens (Greenwich). 2010; 12: 714-720. (C) 2010 Wiley Periodicals, Inc.
Keywords: LOW-DOSE ASPIRIN; PLATELET RESPONSE; DIABETES-MELLITUS; IIIA POLYMORPHISM; BLOOD-PRESSURE; RISK-FACTORS; IN-VITRO; PREVALENCE; NONRESPONSIVENESS; PREVENTION